Development and psychometric pilot-testing of a questionnaire for the evaluation of satisfaction with continuing education in infection control nurses. (July 2018) - Meng, Michael; Peter, Daniel; Mattner, Frauke; Igel, Christoph; Kugler, Christiane
Abstract: Satisfaction with continuing education can be defined as positive attitudes towards educational programs, which has potential to strengthen learning outcomes. A multi-dimensional construct may enhance continuing education program evaluation processes. The objective is to describe the development and psychometric testing of the 'affective - behavioral - cognitive - satisfaction questionnaire' (ABC-SAT) for assessing participants' satisfaction with a continuing education program for nurses in infection control. The multi-staged development of a satisfaction questionnaire comprised of three subscales. The pilot tool was administered to a nationwide sample of 126 infection control nurses to assess satisfaction after participating in a continuing education program. Satisfaction scores were calculated and psychometric testing was performed to determine reliability, using Cronbach's alpha, face validity, objectivity, and economy. A principle component analysis using varimax rotation and Kaiser normalization was performed. The analysis led to a three-factor solution of the questionnaire with 11 items, explaining 61.4% of the variance. Internal consistency of three scales using Cronbach's alpha was 0.83, 0.60, and 0.66, respectively. Selectivity coefficients varied between 0.39 and 0.70. Participants needed approximately three minutes to complete the questionnaire. Initial findings refer to a satisfying scale structure and internal consistency of the 3-dimensional ABC-SAT questionnaire. Further research is required to confirm the questionnaires' psychometric properties.